Amyloidosis in bilateral external auditory canals - Hosoi, Takahiro (BMJ Publishing Group, 2014)
We report a 76-year-old man, a retired farmer, presenting with bilateral external auditory canal obstruction. Skin examination revealed multiple pruritic nodules and periorbital purpura. Ear canal opening surgery was performed. Skin and ear canal biopsy revealed extensive amyloid depositions. Immunoelectrophoresis for urinary Bence-Jones protein was positive, and bone marrow examination showed plasma cell dyscrasia. He received chemotherapy for amyloid light-chain amyloidosis secondary to light-chain multiple myeloma but died from myeloma progression. This case demonstrated how infiltrative conditions such as amyloidosis can lead to bilateral auditory canal obstruction and that the diagnosis of amyloidosis can be missed if a clinician focuses solely on a single organ.